2021
DOI: 10.5194/acp-21-7171-2021
|View full text |Cite
|
Sign up to set email alerts
|

Captured cirrus ice particles in high definition

Abstract: Abstract. Cirrus clouds composed of small ice crystals are often the first solid matter encountered by sunlight as it streams into Earth's atmosphere. A broad array of recent research has emphasized that photon particle scattering calculations are very sensitive to ice particle morphology, complexity, and surface roughness. Uncertain variations in these parameters have major implications for successfully parameterizing the radiative ramifications of cirrus clouds in climate models. To date, characterization of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…We simulate H 2 O mass uptake during the rather short ice formation stage by assuming a simplified ice growth model and approximating the shape of real ice crystals by volume‐equivalent spheres (Section 2.4). To date, it is not possible to fundamentally resolve the issue of ice growth in view of the complexity of cirrus ice particle morphology, complexity, and mesoscopic surface roughness on the one hand (Magee et al., 2021) and due to the absence of a consensus on how real‐world ice crystal habits can be predicted on the other. However, we drop the common assumption of constant ice growth efficiency and use deposition coefficients on ice that depend on ice supersaturation and other variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We simulate H 2 O mass uptake during the rather short ice formation stage by assuming a simplified ice growth model and approximating the shape of real ice crystals by volume‐equivalent spheres (Section 2.4). To date, it is not possible to fundamentally resolve the issue of ice growth in view of the complexity of cirrus ice particle morphology, complexity, and mesoscopic surface roughness on the one hand (Magee et al., 2021) and due to the absence of a consensus on how real‐world ice crystal habits can be predicted on the other. However, we drop the common assumption of constant ice growth efficiency and use deposition coefficients on ice that depend on ice supersaturation and other variables.…”
Section: Methodsmentioning
confidence: 99%
“…Recent balloon‐borne in situ sampling of cirrus ice crystals, combined with cold‐stage electron microscopy, reveals that polycrystalline ice crystals (polycrystals) dominate the habit of cirrus ice crystals (Magee et al., 2021). Even at small sizes, these crystals are sharply faceted and often with hollowed regions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistical data and figures provided by Magee et al [10], the main shape of the ice crystal particles with a size of 1-100 µm is shown in Figure 1. In addition to the immeasurable complex poly-crystals and damaged bullet bodies, among the single particles with modeling significance, the approximate hexagonal prism accounts for the largest number, and its cross-sectional area accounts for the largest proportion of the total area (about 60%).…”
Section: Agglomeration Structural Modelmentioning
confidence: 98%
“…However, with the improvement of the cirrus cloud ice crystal particle capture technology, a clearer understanding of the microscale details of cirrus particles has been attained. In 2021, Magee et al [10] developed a cryoencapsulated balloon system to capture ice particles and observe the microscopic morphology of particles via cryoscanning electron microscopy. They found that cirrus clouds are formed from random clumps of amorphous ice crystals of various shapes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation